2022
DOI: 10.1136/bmjopen-2022-062616
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality of surgical and anaesthesia care in sub-Saharan Africa: a systematic review of hospital-based quality improvement interventions

Abstract: ObjectivesTo systematically review existing literature on hospital-based quality improvement studies in sub-Saharan Africa that aim to improve surgical and anaesthesia care, capturing clinical, process and implementation outcomes in order to evaluate the impact of the intervention and implementation learning.DesignWe conducted a systematic literature review and narrative synthesis.SettingLiterature on hospital-based quality improvement studies in sub-Saharan Africa reviewed until 31 December 2021.ParticipantsM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 97 publications
0
6
0
3
Order By: Relevance
“…Many programs rely on voluntary enrollment, leaving a substantial portion of the population needing more coverage. [ 22 ] Furthermore, there is often an urban-centric focus, with rural and underserved areas receiving less attention and fewer resources. [ 22 ] Geographical barriers, such as the distribution of healthcare facilities, can create access challenges, particularly for rural populations.…”
Section: Barriers and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many programs rely on voluntary enrollment, leaving a substantial portion of the population needing more coverage. [ 22 ] Furthermore, there is often an urban-centric focus, with rural and underserved areas receiving less attention and fewer resources. [ 22 ] Geographical barriers, such as the distribution of healthcare facilities, can create access challenges, particularly for rural populations.…”
Section: Barriers and Challengesmentioning
confidence: 99%
“…[ 22 ] Furthermore, there is often an urban-centric focus, with rural and underserved areas receiving less attention and fewer resources. [ 22 ] Geographical barriers, such as the distribution of healthcare facilities, can create access challenges, particularly for rural populations. [ 23 ] The inaccessibility of healthcare facilities in remote areas further hampers the utilization of health insurance for surgical care.…”
Section: Barriers and Challengesmentioning
confidence: 99%
“…Dalam penelitian Risanti didapatkan hasil adanya hubungan motivasi dengan kepatuhan perawat dalam menerapkan SSC (15). Hasil penelitan tersebut sejalan dengan penelitian yang dilakukan oleh Brima (2022) yang menyatakan bahwa terdapat hubungan antara motivasi dengan kepatuhan perawat dalam pelaksanaan prosedur keselamatan pasien di (7,12,13). Hal ini dikarenakan motivasi merupakan energi yang dapat mendorong seseorang untuk bersemangat melaksanakan pekerjaannya dalam rangka untuk mencapai tujuan yang telah ditetapkan.…”
Section: Metodeunclassified
“…Pendekatan semacam ini dapat menarik seseorang untuk melakukan sesuatu, sehingga munculah motivasi. (13)(14)(15)(16)(17) Pengetahuan perawat tentang SSC di ruang operasi menunjukan bahwa perawat yang memiliki tingkat pendidikan tinggi cenderung memiliki tingkat pengetahuan yang baik (16). Perilaku yang tidak didasari oleh pengetahuan dan kesadaran maka perilaku tersebut tidak akan berlangsung lama.. Hal ini berkaitan dengan perkembangan dari ilmu keperawatan, kedalaman dan luasnya ilmu pengetahuan akan mempengaruhi kemampuan perawat untuk berpikir kritis dalam melakukan tindakan keperawatan.…”
Section: Metodeunclassified
“…Similarly in a systematic review by Brima et al, of the 49 articles that reported hospital-based quality improvement studies in Africa, use of the surgical safety checklist comprised 29% and reduction of surgical site infections comprised 25% ( 15 ). Other interventions well-known to high income settings such as antimicrobial stewardship programs and streamlined postoperative care protocols are lacking in LMICs ( 14 , 15 ). As all countries move toward self-sufficient surgical systems, practical and adaptable guidelines are needed to inform quality improvement initiatives across unique national, regional, and local settings.…”
Section: Introductionmentioning
confidence: 96%